The Discourse Battle on the Establishment of Confucian State University in The Bangka Belitung Islands Province - Pricispa, Izcha; Azzahra, Yang; Putri, Nandini; Herza, Herza (Jurnal Sosiologi Pendidikan Humanis, 2023)
The Province of Bangka Belitung Islands is designated by the central government for the establishment of the Confucian State University (Perguruan Tinggi Negeri/PTN Konghucu). However, the government's initiative to build this Confucian State University has sparked diverse reactions among the residents of Bangka Belitung: some opposing it, some supporting it, and others questioning it. This study analyzed how each party constructs its discourse to sway public opinion. Furthermore, it investigated the social and legal repercussions of this discourse battle, with the intention of providing insights for considerations or recommendations to relevant stakeholders. This research method is descriptive qualitative, involving primary and secondary data collection. Primary data was gathered through direct observation, interviews, and Focus Group Discussions (FGD). Meanwhile, secondary data was sourced from online news, books, journals, and previous research findings. Through this study, researchers identify the varying discourses presented by each party, reflecting both favorable and unfavorable perspectives. Pertarungan Wacana Perguruan Tinggi Negeri Konghucu Di Kepulauan Bangka BelitungBangka Belitung merupakan daerah yang ditunjuk oleh pemerintah pusat sebagai tempat pembangunan Perguruan Tinggi Negeri (PTN) Konghucu. Program pemerintah pusat terkait pembangunan PTN Konghucu ini nyatanya menimbulkan respon yang beragam dari masyarakat Bangka Belitung, ada yang menolak, ada yang mendukung, dan ada pula yang sekadar mempertanyakan. Penelitian ini akan melihat bagaimana wacana yang dikonstruksi oleh masing-masing pihak dalam memenangkan pandangan publik. Lebih lanjut, riset ini juga akan melihat implikasi sosial dan hukum dari hadirnya pertarungan wacana tersebut, dengan diharapkan dapat dijadikan bahan pertimbangan atau rekomendasi kepada pihak terkait. Metode yang digunakan dalam riset ini adalah kualitatif deskriptif dengan proses pengumpulan data primer dan sekuender. Data primer diperoleh langsung melalui observasi, wawancara, dan FGD (Focus Group Discussion), sedangkan data sekunder diperoleh melalui berita online, buku, jurnal dan hasil-hasil penelitian terdahulu. Dari hasil penelitian ini, peneliti menemukan wacana yang dikonstruksikan dari masing-masing pihak yang Pro dan Kontra.